UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN PAI DI SDN UPTD 063 MOMPANG JAE - Alwin Tanjung (Edu Global : Jurnal Pendidikan Islam, 2022)
This research was aimed to find out the difficulties in learning Islamic Education experienced by the fifth grade students at SDN UPTD 063 Mompang Jae, to find out the factors that influenced the fifth grade students’ learning difficulties in learning Islamic Education at SDN UPTD 063 Mompang Jae, and to find out the Islamic Education teacher’s efforts to overcome the fifth grade students’ learning difficulties at SDN 063 Mompang Jae. This research was a descriptive qualitative research. The data was collected by doing observation, interview and documentation. The technique of data analysis was by describing and explaining this research objectively then draw a conclusion by using deductive method. And data validity technique using triangulation, namely source triangulation, data collection technique triangulation and time triangulation. The result of this research showed that: 1) the difficulties in learning Islamic Education experienced by the fifth grade students at SDN UPTD 063 Mompang Jae were the difficulties of fluency in reciting Al-Quran, memorize Al-Quran, understanding the changes in the form of the Hijaiyyah letters that make it difficult for them in doing “ibadah”.. 2) the factors that influenced the fifth-grade students’ learning difficulties in learning Islamic Education at SDN UPTD 063 Mompang Jae were the internal and external factor. 3) the Islamic Education teacher’s efforts to overcome the fifth-grade students’ learning difficulties at SDN 063 Mompang Jae were provide the enough time for students to recite Al-Quran, understanding the students’ characters, choosing the suitable method in learning Al-Quran, creating a good bonding with the students and utilize the technology and doing prayer practice.